Odpowiedzi

Najlepsza Odpowiedź!
2009-11-19T21:36:16+01:00
3m³+2[m²-3(2m-1)]
3m³+2[m²-(6m-3)]
3m³+2[m²-6m+3]
3m³+2m²-12m+6
I podstawiamy:
3*(1/27)+2*(1/9)-12*(1/3)+6 = 2 i 1/3
2009-11-19T21:37:51+01:00
3m³+2[m²-3(2m-1)]= 3m³+2[m²-6m+3]=3m³+2m²-12m+6

m=¹/₃
3(¹/₃)³+2(¹/₃)²-12(¹/₃)+6 =3*1/27+2*1/9-12/3+6=3/27+2/9-12/3+6=3/27+6/27-108/27+6=-99/27+162/27=63/27=2 9/27=2 3/9=2 1/3
2009-11-20T00:43:06+01:00
3m³+2[m²-3(2m-1)] = 3m³+2[m²-6m+3] = 3m³+2m²-12m+6 = 3m³+2m²-12m+6 = 3*(⅓)³+2(⅓)²-12(⅓)+6 = ³/₂₇+²/₉-4+6 = ⅓+2 = 2⅓